STUDI PENERAPAN TEKNIK DASAR KONSELING DI SATUAN PENDIDIKAN TINGKAT SMA/SMK KOTA MADIUN - Widodo, Bernardus (Widya Warta, 2015)
The purpose of this study is to determine the competence of counselors dealing with the application of the basic techniques of counseling in the setting of counseling services at theeducation unit level of Senior High School and Vocational High School in Madiun. This research applied descriptive method with quantitative data in order only to describe variables,symptoms and conditions. The subject is the counselors of Senior High Schools and Vocational High Schools in Madiun. They are 50 in number. In this case, one of their tasks isto provide counseling services both individually and in group. To determine the subject of this study, total sampling technique was used due to the limited number of the subject. Theinstrument used to collect the data was the scale of basic communication skills of counselor.The data analysis made use of mean analysis method. The results showed that the overall mean score obtained by the application of basic techniques of counseling was 2.84. Thisillustrates that the school counselors at the education unit level of Senior High School and Vocational High School in Madiun generally possessed a good ability to apply a number ofbasic techniques of counseling. The application of basic techniques of counseling with a high mean score of the very good category was on the skills of opening (3.83), acceptance (3.75), reflection of feeling (3.25), reassurance (3.01), questioning (3.14), summary (3.19), and termination (3.45); while, the application of basic techniques of counseling with a lower mean score of fair category was on the skills of rejection (1.81), advice (1.86), and restatement (1.92),